Los Factores Socioeconómicos y la Actividad Física de los estudiantes de la Universidad Nacional de Chimborazo. - Aguirre Cuichán, Jennifer Valeria (2024)
ABSTRACT: A socioeconomic study is applied in the city of Riobamba, at the National University of Chimborazo (UNACH) in the period 2023-2s (October 2023-March 2024). The objective of the research was to determine the variables that influence the practice of physical activity of students. Considering socioeconomic factors such as income level, area of origin, hours of leisure, gender, age, marital status, access to facilities and resources, work activity, suffering from diseases, hours of study, consumption of psychoactive substances, and family condition. For data collection, the International Physical Activity Questionnaire (IPAC) was used as a basis and the socioeconomic factors to be studied were added to the survey. The sample of 370 students belonging to UNACH was obtained through stratified sampling. Subsequently, an analysis was carried out with a mixed, non-experimental approach and an estimation using probabilistic regression models. By estimating the Probit model, it was possible to identify which variables are statistically significant. An increase in income, hours of leisure, having access to facilities, not having a partner, not suffering from illnesses that limit exercise, not consuming psychoactive substances and not being parents, are positively associated with the increase in the probability of practicing physical activity.